Microscopic Assistance in Cold Dissection Tonsillectomy – Does it Improve Surgical Outcome? - Dhakal, Ashish; Shrestha, Bikash Lal; Pokharel, Monika; Shrestha, Krishna Sundar; Khadka, Laxmi (Journal of College of Medical Sciences-Nepal, 2022)
Background: Tonsillectomy is one of the commonest surgical procedure carried out by ENT surgeon. In the post-operative period, rate of life-threatening post-operative bleeding varies between 0 and 20 % of the patients. The use of magnifying devices like microscopes or magnifying glasses is still in the focus of clinical investigation as it is hypothesized that precise vision of vessels during surgery allows precise coagulation and therefore reduces post-operative bleeding. Furthermore, precise coagulation should reduce post-operative pain too. The study aims to compare the surgical outcome between microscopic assisted tonsillectomy and traditional cold dissection tonsillectomy. Methods: This prospective study was conducted on 32 patients who had undergone tonsillectomy from March 2020 to December 2021. The patients included in the study underwent cold dissection tonsillectomy where one tonsil was removed with Microscopic assistance and other with traditional cold dissection method with unsupported vision. Intraoperative blood loss was calculated. Post-operative pain score was measured with Wong- Baker FACES® Pain rating scale till 7th post-operative day. Post-operative complications if present were noted. Results: Total of 32 patients were enrolled in the study with age ranging from 16-42 years. There were total 18 male (56.3%) and 14 females (43.8%) in the study. Intraoperative time for Microscopic assisted cold dissection (16.44 ± 3.46 minutes) was longer than Conventional dissection technique (13.94 ± 2.86 minutes) (p=0.04). Amount of blood loss during MCD technique was 16.47 ± 4.58 ml whereas in CD group it was 18.22 ± 4.54 ml (p=0.02). Pain score in both methods were higher during early post-operative period and gradually decreased with time. During rest, there was no statistically significant difference in pain between the two methods during first three post-operative days, after which pain was significantly reduced in MCD through day 4-7 (p <0.05). None of the patient had post- operative hemorrhage requiring intervention in operation room. Conclusions: Microscopic assisted cold dissection showed statistically significant results for reduced intraoperative blood loss and post-operative pain score than Conventional dissection method.